Does self-compassion protect adolescents who are victimized or suffer from academic difficulties from depression?. Issue 3 (3rd May 2020) - Lahtinen, Oskari; Järvinen, Elina; Kumlander, Sonja; Salmivalli, Christina
ABSTRACT: Adolescents face many social and academic difficulties which, if not managed properly, can lead to depression. Self-compassion, a kind and caring orientation towards oneself, has emerged as a possible resilience factor alleviating depression. Self-compassion comprises two factors: self-compassion and self-coldness. The present study set out to investigate whether self-compassion weakens or self-coldness strengthens the association between depression and two difficult circumstances: victimization and academic difficulties (ADs). The sample consisted of 2383 students who had recently made the transition to upper secondary education. The study was cross-sectional and employed a hierarchical regression analysis approach. Strongest interactions were followed up with simple slope analysis. Self-compassion (inversely), self-coldness, ADs, and victimization were statistically significant predictors of depression. Self-compassion weakened the association between ADs and depression. The results suggest encountering difficulties in adolescence and depression are related and that self-compassion may moderate the association.